The Warmia-Mazury Special Economic Zone as a Reason for a Revival of the Local Labour Market - Wysocka, Magdalena; Walkowiak, Ryszard (Olsztyn Economic Journal, 2018)
This article presents the results of studies of the impact of the Special Economic Zone on the situation in the labour market in the Warmińsko-Mazurskie voivodeship. Changes in the number of employees employed by economic entities operating in the Zone as well as changes in the indicators of economic activity of the population in the poviats of the voivodeship were analysed. Data collected during the empirical research showed no impact of the Zone on the improvement of the situation in the local (poviat) labour market.